Remodeling of Hepatocyte Mitochondrial Metabolism and De Novo Lipogenesis During the Embryonic-to-Neonatal Transition in Chickens - Surugihalli, Chaitra; Farley, Linda S.; Beckford, Ronique C.; Kamkrathok, Boonyarit; Liu, Hsiao-Ching; Muralidaran, Vaishna; Patel, Kruti; Porter, Tom E.; Sunny, Nishanth E. (Frontiers in Physiology, 2022)
Embryonic-to-neonatal development in chicken is characterized by high rates of lipid oxidation in the late-term embryonic liver and high rates of de novo lipogenesis in the neonatal liver. This rapid remodeling of hepatic mitochondrial and cytoplasmic networks occurs without symptoms of hepatocellular stress. Our objective was to characterize the metabolic phenotype of the embryonic and neonatal liver and explore whether these metabolic signatures are preserved in primary cultured hepatocytes. Plasma and liver metabolites were profiled using mass spectrometry based metabolomics on embryonic day 18 (ed18) and neonatal day 3 (nd3). Hepatocytes from ed18 and nd3 were isolated and cultured, and treated with insulin, glucagon, growth hormone and corticosterone to define hormonal responsiveness and determine their impacts on mitochondrial metabolism and lipogenesis. Metabolic profiling illustrated the clear transition from the embryonic liver relying on lipid oxidation to the neonatal liver upregulating de novo lipogenesis. This metabolic phenotype was conserved in the isolated hepatocytes from the embryos and the neonates. Cultured hepatocytes from the neonatal liver also maintained a robust response to insulin and glucagon, as evidenced by their contradictory effects on lipid oxidation and lipogenesis. In summary, primary hepatocytes from the embryonic and neonatal chicken could be a valuable tool to investigate mechanisms regulating hepatic mitochondrial metabolism and de novo lipogenesis.